Diel cycles of the particulate beam attenuation coefficient under varying trophic conditions in the northwestern Mediterranean Sea: observations and modeling - Gernez, P.; Antoine, David; Huot, Y. (American Society of Limnology and Oceanography, Inc., 2011)
The changes in shape, amplitude, and timing in the diel variability of the particulate beam attenuation coefficient (cp) were investigated at 4 and 9 m during two seasonal cycles at an oceanic site in the northwestern Mediterranean Sea under contrasting physical and trophic situations. We observed a diel cycle in cp during the winter mixing of the water column, the development of the spring phytoplankton bloom, its collapse, and during the summer oligotrophy. The relative amplitude of the cp diel cycle was about 10–20% during winter mixing and summer oligotrophy and at least twice as large during the spring bloom. Diel cp minima generally occurred around sunrise and maxima a few hours before sunset. The specific particle rate of variation (r) was consistent over the diel cycle, with positive and negative values during daytime and nighttime, respectively. A striking feature of the r diel cycle was a morning maximum, i.e., before solar noon, which was successfully reproduced by a new model of particle assemblage growth rate based on three parameters: maximum growth rate, growth efficiency, and saturation irradiance. Each model parameter undergoes a diel cycle and shows a seasonal variation. A cp-based estimation of the particle net community production is computed from the measurements and model outputs. Results compare favorably with modeled primary production on the basis of continuous measurements of surface chlorophyll using fluorescence.